Effect of CYP3A4, CYP3A5, MDR1 and POR Genetic Polymorphisms in Immunosuppressive Treatment in Chilean Kidney Transplanted Patients - Contreras-Castillo, Stephania; Plaza, Anita; Stojanova, Jana; Navarro, Gustavo; Carmona, Rodolfo; Corvalán, Fernando; Cerpa, Leslie; Sandoval, Christopher; Muñoz, Daniel; Leiva, Marina; Castañeda, Luis E.; Farias, Nayaret; et al. (Frontiers in Pharmacology, 2021)
Cyclosporine (CsA) and tacrolimus (TAC) are immunosuppressant drugs characterized by a narrow therapeutic range and high pharmacokinetic variability. The effect of polymorphisms in genes related to the metabolism and transport of these drugs, namely CYP3A4, CYP3A5, MDR1 and POR, has been evaluated in diverse populations. However, the impact of these polymorphisms on drug disposition is not well established in Latin American populations. Using TaqMan® probes, we determined the allelic frequency of seven variants in CYP3A4, CYP3A5, MDR1 and POR in 139 Chilean renal transplant recipients, of which 89 were treated with CsA and 50 with TAC. We tested associations between variants and trough and/or 2-hour concentrations, normalized by dose (C0/D and C2/D) at specific time points post-transplant. We found that CYP3A5*3/*3 carriers required lower doses of TAC. In TAC treated patients, most CYP3A5*3/*3 carriers presented higher C0/D and a high proportion of patients with C0 levels outside the therapeutic range relative to other genotypes. These results reinforce the value of considering CYP3A5 genotypes alongside therapeutic drug monitoring for TAC treated Chilean kidney recipients.